2003
DOI: 10.1097/01.ju.0000091827.97826.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Administration of Dehydroepiandrosterone on Serum Testosterone Levels and Prostatic Tissue in Rats

Abstract: Oral ingestion of DHEA on a chronic basis in the rat increases serum DHEAS and total testosterone without any evident change in prostate weight or histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…When we compared the experimental group, which was subjected to chronic DHEAS administration over a 6-month period, with the control and sham groups, the serum DHEAS level of the experimental group was determined to be 35 and 38 times higher, respectively; the total testosterone level of the experimental group was determined to be 2 times higher than that of the two other groups (p=0.001). The serum levels of these two substances were determined to be comparable in the control and sham groups, which is concordant with the literature [6-8]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When we compared the experimental group, which was subjected to chronic DHEAS administration over a 6-month period, with the control and sham groups, the serum DHEAS level of the experimental group was determined to be 35 and 38 times higher, respectively; the total testosterone level of the experimental group was determined to be 2 times higher than that of the two other groups (p=0.001). The serum levels of these two substances were determined to be comparable in the control and sham groups, which is concordant with the literature [6-8]. …”
Section: Discussionsupporting
confidence: 91%
“…In the first publication on this issue by Zizzi et al [10], signs of prostatic atrophy were shown in the experimental group. By contrast, Rhoden et al [6] reported no signs of atrophy in either the study or the control group. No variations were observed between the prostate cells of the three groups in terms of atypia in the direction of hypertrophy, hyperplasia, or malignancy; dysplasia; and prostatic intraepithelial neoplasia.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…53-43-0; Natrol Inc., Chatsworth, CA). The dose of DHEA used was 5 mg/kg/day, which is a dose 10 times higher than the usual supplementation dose in humans (Rhoden et al, 2003). In experiments using castrated males and females we also used testosterone propionate and 17-␣-ethynylestradiol, respectively, as positive controls for androgenicity and estrogenicity (see Sections 2.4 and 2.6 below).…”
Section: Chemicals and Dose Selectionmentioning
confidence: 99%